Distinction of Two Zero-Spaced Iron Pipes in GPR Radargram for Engineering Problems - Thabit , Jassim M.; Bakir, Hawkar B. (Iraqi Journal of Science, 2022)
The researchers have tried to focus on how to determine the number of pipes that are present in one obtained hyperbola in radargram profile. Ground Penetration Radar (GPR) survey was performed to distinguish between two zero-spaced iron pipes in radargram. The field work was carried out by constructing artificial rectangular models with dimensions of length, width, and depth equal to 10.0, 1.0, 0.65 meter respectively that filled with dry clastic mixture deposit, three twin sets of air filled iron pipes of 15.24 cm (6 inch) diameter were buried horizontally and vertically inside the mixture at different distances together. Visual and Numerical interpretation were chosen to get the best results. In the visual interpretation, the amplitude variations show that the height of the positive peaks increases with the increase of the space distance between the buried pipes. Numerical interpretation appeared that the decrease in the width of the bands means an increase of the space between the pipes. The second part of the numerical analysis comprises measuring the amplitude value variation, among the signal forms; relying on the value of amplitude in each hyperbola the distinction process becomes quite easy. Depending on the variations in amplitude, the identification and discrimination of two closely spaced underground pipes will be feasible. The big values refer to highly spaced pipes while the low values denote the slightly spaced pipes. It is worth mentioning that the lowest value indicates the amplitude of only one buried iron pipe.